PEMBENTUKAN KARAKTER RELIGIUS MELALUI PEMBIASAAN NILAI ASMAUL HUSNA DI MI NUR AZIZ PROBOLINGGO - Saudah, Siti; Hidayah , Ulil (LPPM STAI Muhammadiyah Probolinggo, 2024)
This research describes the habituation of Asmaul Husna values ​​carried out at MI Nur Aziz Probolinggo to build students' religious character through the implementation of Asmaul Husna values. This research uses a qualitative approach methodology with the research object being MI Nur Aziz Probolinggo students. Data collection techniques use interview, observation and documentation methods. The Asmaul Husna text in this study uses a sample of Asmaul Husna which is applied by teachers to students by practicing the values ​​of daily reading. The research results show that students' religious character is through internalizing the values ​​of Asmaul Husna, namely Ar-Rahman so that students can develop a sense of love, Ar-Rahim so that students can develop a sense of compassion, Al-Malik with leadership and discipline behavior at school, Al-Hamiid carry out commendable behavior at school, Al-Adl behaves fairly towards others, Al-Latiif behaves gently towards others, Al-Halim behaves with good manners, Al-Jami' behaves responsibly towards the tasks given, Al-Afuw forgives each other among others, As-Shabuur behaved patiently in all the trials he faced Keywords: Asmaul Husna; Religious Character; Value Habituation.